2017
DOI: 10.1021/acs.orglett.7b01807
|View full text |Cite
|
Sign up to set email alerts
|

ATP Depletion Assay Led to the Isolation of New 36-Membered Polyol Macrolides Deplelides A and B from Streptomyces sp. MM581-NF15

Abstract: New 36-membered polyol macrolides deplelides A and B were isolated from the culture of Streptomyces MM581-NF15 by bioassay-guided fractionation using an ATP depletion assay. The planar structures of these novel compounds were identified by interpretation of the spectroscopic data (1D/2D NMR, MS, and IR). The relative stereochemistry was partially established using the universal NMR database method and J-based configuration analysis using H-H and long-range H-C coupling constants determined by H NMR or E.COSY a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Difference in macrolactone moiety of compound 1 versus PM100117/8 is the additional methyl group H-44 attached to C-4. Other similar macrolactones of 36 members are described in GT-35 and Deplelides A and B 39 .…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Difference in macrolactone moiety of compound 1 versus PM100117/8 is the additional methyl group H-44 attached to C-4. Other similar macrolactones of 36 members are described in GT-35 and Deplelides A and B 39 .…”
Section: Methodsmentioning
confidence: 80%
“…5c; polyketide open reading frames shown in blue, tailoring genes in yellow). It has biosynthetic similarity to the PM100117/8 family of antitumor compounds 38 (BiG-SCAPE distance of 0.278) and structural similarity to the deplelides 39 , yet has key differences in the macrolide core and glycosylation (Supplementary Figures 3 and 4). The Streptomyces that produce PM100117/8 and deplelide have 99.04% and 98.6% 16S rRNA gene sequence similarity to ISID311, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that O-sulfation of the C-17 hydroxyl group reduces its fungicidal activity while increasing its cytotoxicity. In natural product biosynthesis, sulfation is an unusual, poorly understood phenomenon and there are only a handful of naturally occurring sulfated compounds, such as azinomycin [45], glycopeptide A47934 [49], linear polyenes clethramycin and mediomycins [50], liponucleoside antibiotics Caprazamycins [51], β-lactam sulfated carbapenem MM4550 [52] and deplelides A and B [32]. Enzymatic sulfation has been deployed to increase structural diversity in several classes of natural products [53].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of malonate ester was confirmed by two carbonyl signals at δ C 170.5 and 172.3 but the isolated methylene signals (δ H 3.17 and δ C 43.0) were observed only in DMSO-d 6 and not in methanol-d 4 due to deuterium exchange [17,34]. The placements of malonate ester group and the remaining sulfate group at C-21 [34,35] and C-17 [32], were assigned based on the observed carbon values of δ C 71.0 and 78.2, respectively. From 1D and 2D NMR data, compound 1 was a 32-membered macrocyclic lactone (HMBC: from H-31 to lactone carbonyl) consisting of a sulfate group, a malonate ester, an epoxide, a trisubstituted benzene ring and 2 deoxysugar moieties similar to that of notonesomycin A.…”
Section: Isolation and Identification Of Notonesomycins A (1) And A Nmentioning
confidence: 94%
See 1 more Smart Citation